Long-term supplementation with anthocyanin-rich or -poor Rubus idaeus berries does not influence microvascular architecture nor cognitive outcome in the APP/PS-1 mouse model of Alzheimer's disease. (2nd January 2023) - Alonso Torrens, Aaron; Mitchell, Christopher A.; Pourshahidi, L. Kirsty; Murphy, Brian Óg; Allwood, William; Rizzetto, Lisa; Scholz, Matthias; Tuohy, Kieran; Pereira-Caro, Gema; Moreno-Rojas, José Manuel; McDougall, Gordon; Gill, Chris I. R.
Abstract: Disruption of microvascular architecture is a common pathogenic mechanism in the progression of Alzheimer's disease (AD). Given the anti-angiogenic activity of berry (poly)phenols, we investigated whether long-term feeding of Rubus idaeus (raspberries) could ameliorate cerebral microvascular pathology and improve cognition in the APP/PS-1 mouse model of AD. Male C57Bl/6J mice (50 wild type, 50 APP/PS-1) aged 4-months were fed for 24-weeks, with a normal diet enriched with either 100 mg/day glucose (control diet) or supplemented with glucose and freeze-dried anthocyanin-rich (red) or -poor (yellow) raspberries (100 mg/day) and assessed/sampled post intervention. Cerebral microvascular architecture of wild-type mice was characterised by regularly spaced capillaries with uniform diameters, unlike APP/PS-1 transgenic mice which showed dysregulated microvascular architecture. Long-term feeding of raspberries demonstrated limited modulation of microbiota and no substantive effect on microvascular architecture or cognition in either mice model although changes were evident in endogenous cerebral and plasmatic metabolites.